Application of Bbox-Behnken design with response surface to optimize ventilation system in underground shelter - Mukhtar, Azfarizal; Yusoff, Mohd Zamri; Ng, Khai Ching; Mohamed Nasir, Mohamed Fariz (Penerbit Akademia Baru, 2018)
Ventilation shaft is one of the effective elements in natural venti- lation for ensuring acceptable Indoor Air Quality (IAQ) and thermal comfort. It has been found that the opening of ventilation shaft plays a significant role in the ventilation efficiency of an underground shelter. In this study, we aim to develop a predictive ventilation rate model for a naturally-ventilated un- derground shelter. Computational Fluid Dynamics (CFD) was employed as a simulation tool, where the result was validated with experimental data ob- tained from the previous literature. Goal Driven Optimization (GDO) was used for the optimization process by considering three geometrical factors and their effects on the objective function. From this study, it is found that the predicted response surface values agree well with the CFD values and hence the predictive model is reliable.